Ephemeroptera, Plecoptera and Trichoptera assemblages from riffles in mountain streams of Central Brazil: environmental factors influencing the distribution and abundance of immatures - Bispo, P. C. [UNESP]; Oliveira, L. G.; Bini, L. M.; Sousa, K. G. (Instituto Internacional de Ecologia, 2006)
A influência de fatores ambientais sobre a distribuição de imaturos de Ephemeroptera, Plecoptera e Trichoptera (EPT) foi investigada em riachos do Centro Oeste Brasileiro (Serra do Pireneus, Pirenópolis, Estado de Goiás). Os insetos foram amostrados lavando pedras em frente a um rede (0,5 mm de malhas) e removendo os insetos tanto das pedras quanto das redes. A amostragem foi feita durante 1 h em cinco pontos de coleta em um período de 14 meses. Temperaturas do ar e da água (°C), velocidade da água (m/s), vazão (m³/s), condutividade elétrica (µS/cm), pH, e precipitação pluviométrica (mm) também foram registradas. em geral, podemos afirmar que a altitude, a classificação hidrológica (ordem) e a cobertura vegetal foram os fatores mais importantes na distribuição de imaturos de Ephemeroptera, Plecoptera e Trichoptera. A influência da precipitação pluviométrica sobre a variação temporal da abundância foi maior em trechos de ordem média (3ª, 4ª ordem) quando comparado aos menores riachos (primeira ordem).

The influence of environmental factors on the distribution of Ephemeroptera, Plecoptera and Trichoptera (EPT) immatures was investigated in streams of the Brazilian Center-West (Serra do Pireneus, Pirenópolis, State of Goiás). The insects were sampled by lifting the stones in front of a sieve (0.5 mm mesh) and then removing the insects from both the stone and the sieve. Sampling was carried out for 1 h at 5 collection sites over a period of 14 months. Air and water temperature (°C), water velocity (m/s), discharge (m³/s), electric conductivity (µS/cm), pH, and rainfall (mm) were also recorded. In general, we may state that altitude, hydrologic classification (order) and vegetation cover were the most important factors explaining the distribution of Ephemeroptera, Plecoptera and Trichoptera immatures. The influence of the rainfall on the temporal variation of the abundance of insects was stronger in stream segments of medium order (3rd, 4th order) compared to smaller streams (first order).
Comunidades de Ephemeroptera, Plecoptera e Trichoptera em riachos de montanha do Brasil Central: fatores ambientais influenciando a distribuição e abundância
Keywords: Ephemeroptera; Plecoptera; Trichoptera; ambientes lóticos; distribuição larval; Ephemeroptera; Plecoptera; Trichoptera; lotic environments; larval distribution